Role of cardiac–renal neural reflex in regulating sodium excretion during water immersion in conscious dogs - Miki, Kenju (Blackwell Science Inc, 2002)
The present study was undertaken to determine the role of cardiopulmonary mechanoreceptors in inducing the sustained reduction of renal sympathetic nerve activity (RSNA) and concomitant changes in sodium excretion occurring during water immersion (WI) in intact dogs. Seven cardiac-denervated dogs were chronically instrumented for measuring RSNA, systemic arterial (P(a)), central venous (P(cv)) and left atrial pressures (P(la)). WI initially decreased RSNA in cardiac denervated dogs by 10.0 ± 5.5 %; thereafter the RSNA fell to a nadir of 18.5 ± 5.6 % (P < 0.05) at 40–80 min of WI and then returned toward the pre-immersion level. Renal sodium excretion increased significantly by 211 ± 69 % (P < 0.05) only during the first 20–40 min of WI. WI increased P(a), P(cv) and P(la) in a step manner from 94 ± 3 to 108 ± 3 mmHg (P < 0.05), from 1.4 ± 0.5 to 12.3 ± 1.0 mmHg (P < 0.05) and from 4.9 ± 0.6 to 15.4 ± 1.2 mmHg (P < 0.05), respectively. These responses in RSNA and sodium excretion to WI in the cardiac-denervated dogs were significantly (P < 0.05) attenuated compared with those in a previous group of intact dogs. These data suggest that the attenuated responses of neural and excretory response to WI observed in cardiac-denervated dogs can be attributed to an interruption of afferent input originating from the cardiopulmonary mechanoreceptors to the central nervous system.